DOPPLER FLOWMETRY IN SEVERE PREGNANCY HYPERTENSIVE DISEASE STUNTED ITRAUTERINO - Quispe, José (2015)
OBJECTIVE: To determine the role of Doppler ultrasonography of umbilical, uterine and medial cerebral arteries in the management of hypertensive disease with intrauterine growth retardation (JUGR) and its association with adverse perinatol results. MATERIAL AND METHODOS: Retrospective study done at Ecomed ultrasound center32 of 158 patients were chosen because of high risk pregnancy. Fetal wellbeing and uterine, umbilical and cerebral arteries Doppler velocimetry were determined, looking for JUGR and alterations of maternal and fetal Doppler, consisting of uni or bilateral uterine artery notch and decrease of uterine artery umbilical artery resistance ratio, that normally is above 1. Umbilical artery Doppler with absent diastole and reverse flow were considered ominous fetal signs. Serial studies were performed to determine the obstetrical conduct. Patients were followed up to the end of pregnancy and later the evolution of newborns at ICU was determined to know neonatal morbidity and mortality. CONCLUSIONS: Pregnancy hyperiensive disease with intrauterine fetal growth retardation is cause of perinatal morbidity and mortality, when associated to abnormal fetal Doppler velocimetry. The presence of notch in uterine artery could be diagnostic element to predicttoxemia and intrauterine growth retardation. Fetal wellbeing modified test could be implemented to obtain better perinatal results. Key words: Pregnancy hypertensive disease, intrauterine growth retardation, Doppler velocimetry of uterine, umbilical and medial cerebral arteries.